2016
DOI: 10.1111/jmp.12212
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of kisspeptin and kisspeptin receptor in the primate testis

Abstract: Kisspeptin receptor and kisspeptin are localized in the testis of Old World and New World primates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Tariq et al [17] reported KISS1 expression in spermatocytes and spermatids (i.e., immature sperm cells) versus the presence of KISS1R in spermatocytes and Sertoli cells, measured by dual immunocytochemistry and RT-PCR. Similar to rodents [19][20][21], Irfan et al [18] reported KISS1 expression in Leydig cells of adult primates by immunocytochemistry. In accordance with the other study in adult monkeys [17] and to findings in amphibians [24], KISS1R was detected in Sertoli cells.…”
Section: Distribution Of Kisspeptin and Its Receptormentioning
confidence: 83%
See 2 more Smart Citations
“…Tariq et al [17] reported KISS1 expression in spermatocytes and spermatids (i.e., immature sperm cells) versus the presence of KISS1R in spermatocytes and Sertoli cells, measured by dual immunocytochemistry and RT-PCR. Similar to rodents [19][20][21], Irfan et al [18] reported KISS1 expression in Leydig cells of adult primates by immunocytochemistry. In accordance with the other study in adult monkeys [17] and to findings in amphibians [24], KISS1R was detected in Sertoli cells.…”
Section: Distribution Of Kisspeptin and Its Receptormentioning
confidence: 83%
“…Furthermore, re-expression of KISS1R in GnRH neurons is insufficient to normalise testicular function, suggesting a potential direct role of KISS1/KISS1R in testis physiology [15]. Studies in primates [16][17][18], rodents [19][20][21], amphibians [22][23][24] and fish [25,26] have observed potential regulatory roles of kisspeptin in germ cell progression, modulation of sperm function and testicular steroidogenesis. In this review, we discuss evidence of local expression of KISS1/KISS1R system in the testes and its role in direct testicular functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, humans with mutations in the KISS1R gene, or mice with mutations in KISS1 or KISS1R genes, are affected by hypogonadotropic hypogonadism, characterized by deficient production of gonadotropins and sex steroids, which leads to an incomplete sexual maturation [37][38][39][40][41]. Recent evidence has shown that they can also be found in mammalian reproductive tissues, including the testes [42,43], the uterus [26,29,[44][45][46], the oviduct [26,47], the ovary [26][27][28][48][49][50][51][52], and the placenta [53].…”
Section: Kisspeptinsmentioning
confidence: 99%
“…As for kisspeptins and/or KISS1R, there is documented evidence of their expression in the following tissues and cell types: round spermatid cells of mice [72]; primordial germ cells, Leydig, and interstitial cells of mice [73]; human spermatozoa [43]; Sertoli cells and interstitial compartment of rhesus monkeys [42]; and Leydig cells, Sertoli cells, and all germ cells of Pelophylax esculentus frogs [74].…”
Section: Expression Of Tachykinins and Kisspeptins In Testicular Tissuesmentioning
confidence: 99%